Parametric performance simulation of a proximity-coupled fed microstrip dipole array - Soh, Ping Jack; Amir Razif Arief, Jamil Abdullah; Aiza, M. M.; Azremi, Abdullah Al Hadi; Abdul Aziz, M.Z A; Rahim, M.K A (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org